Evidence and Consequences of the Central Role of the Kidneys in the Pathophysiology of Sympathetic Hyperactivity - Vink, Eva E.; Blankestijn, Peter J. (Frontiers in Physiology, 2012)
Chronic elevation of the sympathetic nervous system has been identified as a major contributor to the complex pathophysiology of hypertension, states of volume overload -such as heart failure- and progressive kidney disease. It is also a strong determinant for clinical outcome. This review focuses on the central role of the kidneys in the pathogenesis of sympathetic hyperactivity. As a consequence, renal denervation may be an attractive option to treat sympathetic hyperactivity. The review will also focus on first results and the still remaining questions of this new treatment option.